Comparative Analysis of Bias Index to Determine The Density of Pertalite and Pertamax Fuel Oil Using Snellius's Law - Ramadhan, Purwo Harris; Dannial, Mohammad; Ulfa, Juliana; Nurhafifah, Zeinab; Kusumah, Fuji Hernawati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The refractive index value can be determined using various methods, one of which is the principle of Snell's law. . This research aims to compare the refractive index of Pertalite and Pertamax fuel oil and prove Snell's law. This research was conducted at the Optical Laboratory of the Tadris Physics Study Program, Syarif Hidayatullah State Islamic University, Jakarta. The main materials used are Pertamax and Pertalite as the fluid, then laser, ruler, glass container, pen, protractor, HVS paper. The results obtained from this experiment, namely the refractive index value for Pertalite, obtained an average value of 1.36 and for the refractive index for Pertamax, the average value was 1.653, so it can be concluded that the refractive rays in Pertamax are greater than the refractive rays in Pertalite. So, for its use, Pertamax is more efficient compared to Pertalite.Keywords: Refractive index, refraction, pertalite, and Pertamax